Revealing room temperature ferromagnetism in exfoliated Fe5GeTe2 flakes with quantum magnetic imaging. (1st April 2022) - Chen, Hang; Asif, Shahidul; Whalen, Matthew; Támara-Isaza, Jeyson; Luetke, Brennan; Wang, Yang; Wang, Xinhao; Ayako, Millicent; Lamsal, Saurabh; May, Andrew F; McGuire, Michael A; Chakraborty, Chitraleema; et al.
Abstract: Van der Waals (vdW) material Fe5 GeTe2, with its long-range ferromagnetic ordering near room temperature, has significant potential to become an enabling platform for implementing novel spintronic and quantum devices. To pave the way for applications, it is crucial to determine the magnetic properties when the thickness of Fe5 GeTe2 reaches the few-layers regime. However, this is highly challenging due to the need for a characterization technique that is local, highly sensitive, artifact-free, and operational with minimal fabrication. Prior studies have indicated that Curie temperature T C can reach up to close to room temperature for exfoliated Fe5 GeTe2 flakes, as measured via electrical transport; there is a need to validate these results with a measurement that reveals magnetism more directly. In this work, we investigate the magnetic properties of exfoliated thin flakes of vdW magnet Fe5 GeTe2 via quantum magnetic imaging technique based on nitrogen vacancy centers in diamond. Through imaging the stray fields, we confirm room-temperature magnetic order in Fe5 GeTe2 thin flakes with thickness down to 7 units cell. The stray field patterns and their response to magnetizing fields with different polarities is consistent with previously reported perpendicular easy-axis anisotropy. Furthermore, we perform imaging at different temperatures and determine the Curie temperature of the flakes at ≈300 K. These results provide the basis for realizing a room-temperature monolayer ferromagnet with Fe5 GeTe2 . This work also demonstrates that the imaging technique enables rapid screening of multiple flakes simultaneously as well as time-resolved imaging for monitoring time-dependent magnetic behaviors, thereby paving the way towards high throughput characterization of potential two-dimensional (2D) magnets near room temperature and providing critical insights into the evolution of domain behaviors in 2D magnets due to degradation.